The American economy : the struggle for supremacy in the 21st century - Spulber, Nicolas (Cambridge [England] ; New York, NY, USA : Cambridge University Press, 1995)
This work focuses on the economic challenges the American economy has met during the post-World War II era and on the new challenges - represented notably by the competing economies of Japan, Germany, and the entire European Union - which confront it as the 21st century approaches. The book shows how the transformations brought about by international competition fit into the long-term processes of economic growth and change with respect to structural mutations, technological development, the role of government, and the evolution of government-business relations. Professor Spulber presents a detailed critique of the thesis alleging that the American economy has experienced some kind of decline. He demonstrates not only that such a decline has not taken place but also that the economy will continue to strengthen if growth and change are primarily left to emerge from the impulses and incentives of the private economy.
Pt. I. A challenge met. 1. Postwar growth and change. 2. Government-business relationship -- Pt. II. The new challenge and its implications. 3. The challenge. 4. The implications -- Pt. III. The long-run development of the U.S. economy. 5. The structural transformations. 6. The state machine and the evolving economy -- Pt. IV. The road ahead. 7. New priorities. 8. Contests at technological frontiers.
Includes bibliographical references (p. 253-277) and index.
Rasal
Keywords: Competition, International; United States -- Economic conditions